The influence of accountant competence and accounting applications on the quality of financial reports which impacts the determination of tax payment values. - teddy; Ida Rosnidah; Irwan Sutirman (LP2M IAIN Palopo, 2026)
The quality of financial reports plays a crucial role in ensuring accurate and fair determination of tax payment values. This study aims to analyze the influence of accountant competence and the use of accounting applications on the quality of financial reports and their subsequent impact on tax payment determination. Accountant competence is reflected in technical skills, professional knowledge, and compliance with accounting standards, while accounting applications are viewed as tools that support accuracy, efficiency, and consistency in financial data processing. This research employs a quantitative approach by examining the relationships between accountant competence, accounting applications, financial report quality, and tax payment values. The findings indicate that higher accountant competence and effective utilization of accounting applications contribute positively to the quality of financial reports. Improved financial report quality, in turn, enhances the reliability of tax calculations and supports proper tax payment determination. These results highlight the importance of continuous professional development for accountants and the adoption of reliable accounting applications to strengthen financial reporting and taxation processes. This study is expected to provide practical insights for organizations, policymakers, and tax authorities in improving financial reporting quality and tax compliance.